2017
DOI: 10.1021/acs.joc.6b02893
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Recyclization of 1H-Indoles for Synthesis of 2-Indolylbenzoxazinones via Cleavage of the C2–C3 Bond with AIBN under Air

Abstract: A novel and concise method for the oxidation of unprotected indole derivatives to synthesize 2-indolylbenzoxazinones in the presence of AIBN under open air has been successfully demonstrated. This metal-free reaction is both atom- and step-efficient and is applicable to a broad scope of substrates. This new methodology provides a facile pathway for oxidative C2-C3 bond cleavage and recyclization of 1H-indoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…As a consequence, substantial efforts have been devoted to the synthesis and functionalization of indoles, [2] including molecule editing such as a skeletal rearrangement [3] . In conventional indole editing, the C2‐C3 bond‐breaking transformation achieved by oxidative cleavage, [4a–c] and ring‐expansion with alkyne moieties, [4d–e] which require harsh conditions or transition metals. In 2021, Levin and co‐workers reported the use of new azine reagents as carbynyl cation equivalents to edit indole ring involving the C2‐C3 bond‐breaking transformation, affording quinolines (Scheme 1A) [5] .…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, substantial efforts have been devoted to the synthesis and functionalization of indoles, [2] including molecule editing such as a skeletal rearrangement [3] . In conventional indole editing, the C2‐C3 bond‐breaking transformation achieved by oxidative cleavage, [4a–c] and ring‐expansion with alkyne moieties, [4d–e] which require harsh conditions or transition metals. In 2021, Levin and co‐workers reported the use of new azine reagents as carbynyl cation equivalents to edit indole ring involving the C2‐C3 bond‐breaking transformation, affording quinolines (Scheme 1A) [5] .…”
Section: Methodsmentioning
confidence: 99%
“…Activation of the Ant amide bond fragmentations in the presence of strong acid, suggesting that these reactions proceed via an acid-promoted activation of the amide followed by an intramolecular cyclization mechanism. [80][81][82] Fortunately, we found that if the next amino acid was coupled (Thr), then only small amounts of the benzoxazinone fragment was detected. Upon analyzing this elongated peptide (where the Thr has been attached) by HPLC-MS, we determined that the reaction of peptide 2.44 and 2.22 using triphosgene/2,4,6-collidine was sluggish and required 19 h to be completely converted into peptide 2.45.…”
Section: The Synthesis Of Sclerotide Amentioning
confidence: 90%
“…The conventional synthetic routes rely mainly on the cyclization of anthranilic acids and their derivatives, or alternatively, the condensation of isotonic anhydrides with other acid derivatives [16] or the oxidation of 2-aryl indoles. [17] In recent years, transition-metal-catalyzed or mediated [18] and organocatalyzed [19] reactions provide new powerful tools for the construction of 4H-benzo[d] [1,3]oxazin-4-ones.…”
Section: Introductionmentioning
confidence: 99%